If a = true , b = false , c = true then (a and b and c) = ?
To me this question is nonsense but Alan already answered it anyway.
Added later: Boolean logic - yes I should have realised.
This is a question of Boolean logic, where the logic table for AND looks like:
Alternatively, think of AND as multiply, true as 1 and false as 0.
So it just means " A and B and C are all true."
And the answer is false ?
No. If you think of AND as "multiply", with "true" as 1, and "false" as 0; then
a=1, b=0, c=1 so (a and b and c) becomes 1*0*1 which is 0.
Since 0 represents false, then (a and b and c) = (true and false and true) = false.
Thanks Alan but can you give an example of when my interpretation is wrong?
If they are not all true there will be a 0 on the mix. When multiplied the answer will be 0 so the answer will be false.
Err.. Your post said "So it just means " A and B and C are all true." And the answer is false ?"
If you meant "So it just means " A and B and C are not all true." then, yes, the answer is false. If they are all true the answer is true.
No I meant that the statement is "A , B and C are all true."
And the statement is clearly false.
Here's my take on this.......
T ^ F ^ T =
(T ^ F) ^ T =
(F) ^ T =
To verify this....here's is the truth table for a^b^c = p^q^r....the third row shows the result for T^F^T
Melody, I don't think the combination (a and b and c) should be read as "a and b and c are true" any more than the combination 1*0*1 should be read as "1*0*1 = 1".
However, I guess I'm still not understanding your meaning!
I am not saying that the statement is true I am saying that it is a statement and the statement is false.
Statement: All dogs have 5 legs and all cats are mammals.
This logic statement is FALSE
In your example the statement is 1*0*1=1 And this statement is FALSE. I don't particlualy like the zero and one analogy but I can see that it also works.